Type 2 diabetes after gestational diabetes: greater than fourfold risk among Indigenous compared with non‐Indigenous Australian women†. Issue 2 (22nd October 2015) - Chamberlain, Catherine R.; Oldenburg, Brian; Wilson, Alyce N.; Eades, Sandra J.; O'Dea, Kerin; Oats, Jeremy J. N.; Wolfe, Rory
Abstract: Background: Gestational diabetes is associated with a high risk of type 2 diabetes. However, progression rates among Indigenous women in Australia who experience high prevalence of gestational diabetes are unknown. Methods: This retrospective cohort study includes all births to women at a regional hospital in Far North Queensland, Australia, coded as having 'gestational diabetes' from 1 January 2004 to 31 December 2010 (1098 births) and receiving laboratory postpartum screening from 1 January 2004 to 31 December 2011 ( n  = 483 births). Women who did not receive postpartum screening were excluded from the denominator. Data were linked between hospital electronic records, routinely collected birth data and laboratories, with sample validation by reviews of medical records. Analysis was conducted using Cox‐proportional regression models. Results: Indigenous women had a greater than fourfold risk of developing type 2 diabetes within 8 years of having gestational diabetes, compared with non‐Indigenous women (hazards ratio 4.55, 95% confidence interval 2.63–7.88, p  < 0.0001). Among women receiving postpartum screening tests, by 3, 5 and 7 years postpartum, 21.9% (15.8–30.0%), 25.5% (18.6–34.3%) and 42.4% (29.6–58.0%) Indigenous women were diagnosed with type 2 diabetes after gestational diabetes, respectively, compared with 4.2% (2.5–7.2%), 5.7% (3.3–9.5%) and 13.5% (7.3–24.2%) non‐Indigenous women. Multivariate analysis showed an increased risk of developing type 2 diabetes among women with an early pregnancy body mass index ≥25 kg/m 2, only partially breastfeeding at hospital discharge and gestational diabetes diagnosis prior to 17 weeks gestation. Conclusions: This study demonstrates that, compared with non‐Indigenous women, Indigenous Australian women have a greater than fourfold risk of developing type 2 diabetes after gestational diabetes. Strategies are urgently needed to reduce rates of type 2 diabetes by supporting a healthy weight and breastfeeding and to improve postpartum screening among Indigenous women with gestational diabetes. Copyright © 2015 John Wiley & Sons, Ltd.